?????? ???????? ???? ???????? ?? ?????? ????????? / EL-HUKÛKU'S-SIYÂSIYYEH LI ĞAYRI'L–MÜSLIMIN FÎ'DDEWLETI'L-İSLMIYYEH - ABDULQADIR, SHAWKAT FATAH (Fırat Üniveristesi, 2021)
Bu çalışma, İslami delillerde gayrimüslimlerin siyasî haklarını tespit ve tahlil etmeyi ve bu hususta hukukçuların söz ve görüşlerini delillerin izahıyla birlikte incelemeyi amaçlamaktadır. Bu araştırma bir giriş bölümü, üç bölüm ve bir sonuç içermektedir: Giriş bölümünde, araştırmanın konusu ve amaçları tartışılmış olup, gayrimüslimlerin türleri ve İslam devletine katılımları hakkında bir açıklama ile hak kavramları, Asya ve gerçekleri hakkında bilgilendirici bilgiler verdik. Birinci bölümde: Gayrimüslimlerin siyasî haklarından ve İslam devletindeki teminatlarından bahsettik. İkinci bölümde: (oy kullanma, aday olma, parti kurma, ittifaklar, muhalefet ve hükümet işleri) dahil olmak üzere siyasi hakların türlerini İslam devletine katılım örnekleri ile konuştuk ve İslam'ın üzerinde konumlandırın. Üçüncü bölümde ise hakların özellikleri ve kontrolleri hakkında bilginlerin bu kontrollerin önemi ve bu kontrolleri gayrimüslimler tarafından ihlal edilmesinin hükmü hakkında görüşlerini açıklayarak konuştu. Gayrimüslimlerin bu hakların İslam devletinde anayasaya ve İslam devletinin kanunlarına uyduğu sürece meşruiyetinde özetlenebilecek ulaştığım en önemli bulgu ve önerilerle bu araştırmayı sonlandırdım.

This Study aims to establish and analyze the political rights of non- Muslims in the Islamic state, and to review what schoolers have being saying and their opinions in relations to this matter, and indicating to the related evidence. This research contains a preface chapter, three chapters and a conclusion: In the preface chapter we talked about objectives of the research and its aims and we gave brief information about the concepts of rights and politic and its reality, with a clarification of non-Muslim categories and their participation in the Islamic state. In the first chapter, we talked about the political rights of non-Muslims and the guarantees of these rights in the Islamic state. In the second chapter, we talked about the types of political rights, including (The right to vote, to candidacy, to form parties, alliances, and become an opposition and the right to political asylum, citizenship, and assignment to a governmental employment) and indicating to examples in relation to their participation in the Islamic state, and the position of Islam towards these rights. In the third chapter, I talked about the characteristics and controls of these rights, mentioning the opinions of scholars about the importance of these controls and the ruling on non-Muslims violating these controls. I concluded this research with the most important outcomes and suggestions that I came out with, that can be summarized in the legitimacy of these rights for non-Muslims in the Islamic state, as long as they respect the constitution, and commitment to the laws of the Islamic state.
I?slam devletinde gayr-i Müslimlerin siyasi hakları / The political rights of "non-Muslims in the Islamic state"
Keywords: Din